Порівняльний аналіз інтернет-протоколів mqtt та coap для використання в інтернеті речей - Доля, А. С. (ХНУРЕ, 2023)
New technologies for the remote communication of software and hardware packages for automatic control of smart homes and technological processes are considered. The comparative analysis of contemporary protocols for the most prospective technology “internet of things” (IoT) is given. IoT is a system of interrelated computation devices and digital actuating mechanisms that are supplemented with the ability to transfer data over the internet without any human interaction. Industrial applications of IoT (industrial internet of things, IIoT) require more fast and reliable protocols than HTTP or WebSocket. Some advantages and disadvantages of MQTT and COAP protocols for the next IIoT systems are shown up and discussed.